2021
DOI: 10.1002/leg3.121
|View full text |Cite
|
Sign up to set email alerts
|

The effects of crosslinking agents on faba bean flour–chitosan‐curcumin films and their characterization

Abstract: Although glutaraldehyde (GLU) has been frequently preferred to improve some characteristics of bio-degradable food packages, it is regarded as a hazardous chemical.Therefore, in this study, the possibility of replacement GLU with citric acid (CA) a non-toxic compound was questioned in a film formation. Different ratios of GLU and CA on faba bean flour, chitosan, and curcumin film were examined. To determine the most favorable film composition, water solubility (WS), swelling degree (SD), water contact angle (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 66 publications
0
6
0
1
Order By: Relevance
“…Table 6 shows the Tg, Tm (along with onset and end temperatures), as well as degradation temperatures of the films. The films show a semi-crystalline structure due to the presence of both Tg and Tm, and the fibers mostly remain in a non-crystalline state as a result of elongating and rapidly solidifying during electrospinning [23]. GL films melt at a similar temperature to that studied in bovine gelatin films earlier [39] but show a higher Tg than gelatin films produced through casting [40].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 88%
See 2 more Smart Citations
“…Table 6 shows the Tg, Tm (along with onset and end temperatures), as well as degradation temperatures of the films. The films show a semi-crystalline structure due to the presence of both Tg and Tm, and the fibers mostly remain in a non-crystalline state as a result of elongating and rapidly solidifying during electrospinning [23]. GL films melt at a similar temperature to that studied in bovine gelatin films earlier [39] but show a higher Tg than gelatin films produced through casting [40].…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 88%
“…where Ic is the integrated intensity of the crystalline phase and Ia is the integrated intensity of the amorphous phase [23].…”
Section: X-ray Diffractionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fattahi et al [ 17 ] found that sonication as a high-energy homogenization technique, strengthens the mechanical and antimicrobial properties of films incorporating essential oils. Yildiz et al [ 18 ] found that pea flour-based edible film, when treated with sonication, had significantly increased crosslinking of the biopolymers and improved physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Los materiales desarrollados mejoran la capacidad antimicrobiana contra Escherichia coli y Staphylococcus aureus, además de una ligera mejora en las propiedades mecánicas y de barrera. En el trabajo desarrollado por Yildiz et al [165], se estudian las películas formadas por proteínas de haba, empleando mezclas con quitosano, curcumina y ácido cítrico como agente de entrecruzamiento. Los resultados demuestran un incremento en la hidrofobicidad, además de una mejora en las propiedades barrera de las películas, con lo cual es posible su uso como material de envase activo para alimentos.…”
Section: I421 Aplicaciones De Películas a Base De Proteínasunclassified